La questione della narrazione. Tra filosofia e letteratura. In dialogo con Paul Ricœur - Caputo, Annalisa (Itinerari, 2024)
The essay intertwines, on the one hand, some Ricœurian reflections on narrative, storytelling, and narrative identity, and on the other hand, a particular image by Rembrandt: Aristotle with a Bust of Homer. After a more general introduction – emphasizing the difficulty (but also the necessity) of distinguishing words and themes such as ‘literature’, ‘story’, ‘narrative’, and ‘narrativity’, – two main issues are addressed: the relationship between literature and other human linguistic and artistic dimensions (within the common experience of mimesis); and the importance of stories for the structuring of the Self (narrative identity). The open conclusion shifts to the role that philosophy – and theoretical philosophy in particular – can (and perhaps must) have in relation to literature, and in relation to the choice of literary/narrative models that inevitably mark the fields of education and politics.